Recreational load as a driving variable for urban forests - I. Kupka (Journal of Forest Science, 2006)
Green areas and urban forests represent important factors of urbanized environment which attracts more and more attention of forest management and silviculture. Recreational load and its types are the most important driving variable for the management framework in which basic silvicultural methods should be applied. The problem of the required combination of natural and social limits is resolved by a matrix which takes into account forest ecosystem quality and recreation. The matrix defines 9 or 27 units (their number depends on the fact if we take into account the age of stand or not) for which basic management rules could be prepared. The basic rules concerning biological aspects are described in a general way in the article.